Presence of Pathological Arrhythmia in Patients Admitted to the Emergency Room for Cardiac Arrhythmia - Umer Jaleel Rana, Liaquat Ali, Riffat Siddiqui, Hina Azeez, Saad Ahmad, Ahtisham Ul Hassan, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The presence of a patient with indications brought on by cardiac arrhythmia is a regular condition that brings them to the emergency room. Nonetheless, up to this point, the incidence of abnormal heart rhythm among children who have been triaged for cardiac arrhythmia in our emergency department is unclear. Methods : The design of this study was prospective observational study design. This study was conducted in Pakistan Institute of Medical Sciences and the duration of this study was from January 2021 to April 2021. 345 patients in the emergency department (ED) or after admission, a workup consisting of echocardiography was conducted at discretion of treating physician. The examinations remained carried out by cardiology residents or associates who had previous experience with echocardiography. To use the individuals' initial electrocardiogram (ECG) following admission, patients were categorized as either having a "pathological heart rhythm" or having a "norm recurrent sinus rhythm." This was done so that additional investigation could be performed. Individuals whose heart rates fall inside the current range often do not exhibit any symptomatology of bradycardia or tachycardia that need medical care, which led to the definition of norm frequent SR as SR occurring at a heart rate of between 50 and 100 beats per minute. Every single heart rhythm that was dissimilar from the form of frequent SR was considered to be a pathological heart rhythm Results: Individuals who had been triaged and referred to multidisciplinary emergency department of Pakistan Institute Of Medical Sciences (PIMS), Islamabad for cardiac arrhythmia treatment during the previous year remained involved in the current retrospective cohort research. After that, the therapeutic approach, admission frequency, and diagnoses at discharge were examined, as well as the heart rhythm as shown on the 12-lead ECG. Out of a maximum of 37,850 individuals, there were a maximum of 552 who were referred to a specialist for cardiac arrhythmia. On the first ECG, 43.6% of those individuals had a pathological heart rhythm, with 65.8% of them having atrial fibrillation, 17.6% had atrial flutter, and 18.6% having other heart rhythm abnormalities. Approximately 83% of patients walked in with emergency severity index III problems, which means that numerous resources are required but vitals are not urgent. Patients with a pathological electrocardiogram have always been taken to the hospital at a rate of 62 percent, while only 64 percent of patients with a sinus rhythm had been admitted. Additionally, 35.8 percent of the patients with a pathological electrocardiogram undertook invasive investigations, compared to 15.7 percent of the patients in the sinus rhythm cohort. The diagnosis of cardiac arrhythmia had already been present in 46.5% of patients due to their past interactions with medical professionals. Practical Implication: This study was to figure out the patients who had a pathological heart rhythm, as well as the actual preponderance of this condition among these patient populations, and to assess additional medical treatment, successive hospitalization, and the primary diagnostic test made upon discharge Conclusion: It was determined that cardiac arrhythmia was present in a total of 2.9% of the individuals who presented themselves to our multidisciplinary emergency department. The hospital admission rate was fairly high, coming up at 48.6%, although the patients who presented themselves to the emergency room in our sample were seldom in a life-threatening state. Because such a significant number of people in our sample had a previous history of cardiac arrhythmia, improved outpatient care among those individuals is required in order to cut down on trips to the emergency department also save costs. Keywords: Cardiac Arrhythmia, Pakistan Institute Of Medical Sciences, Emergency Room.